Design Thinking Approach in Handling Food Waste In PT Atim and Wanti Saiyo Jaya Catering Business - Taryana, Asep; Kalsum, Ummi; Yatim, Md Ivan Zachary; Azman, Muhammad (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Waste and environmental management are important factors to improve the quality of life of the community. As a business actor, especially a business engaged in the F&B sector, innovation in managing waste generated from their business is one of the major challenges to the sustainability of a business. Thus, the topic related to handling food waste in this food business is considered important to study. Purpose: This study aims to obtain solutions in handling food waste that can be done to minimize the impact caused by food waste produced by the catering business of PT Atim and Wanti Saiyo Jaya. Design/methodology/approach: The analysis of problems and solutions in this study uses a qualitative approach with the design thinking method. Findings/Results: The results of the analysis show that this business's ability to process food waste is still lacking so it ends up in a landfill, which is widely complained about by the local community. Internal training, creating a waste cycle process, and establishing partnerships are alternative solutions that can be done to overcome these problems. Conclusion: The design thinking approach is one of the comprehensive alternatives to help business people in mapping problems and finding solutions to these problems. Originality/Value (State of The Art): The catering business of PT Atim and Wanti Saiyo Jaya is a catering business that has been established for quite a long time. The support of the government, community, and private sector in improving waste management can help this catering business become a more sustainable business. Keywords: environment, food waste, design thinking, catering business, waste management